The Relationship Between Work Engagement and Performance: A Review of Empirical Literature and a Proposed Research Agenda. (September 2013) - Kim, Woocheol; Kolb, Judith A.; Kim, Taesung
Engagement has been defined in a variety of ways. Engagement in the workplace generally is viewed as a positive, fulfilling, affective-motivational state of work-related well-being. Due to its structural relationship between antecedents (e.g., job resources and personal resources) and consequences (e.g., performance and turnover intention), work engagement has been receiving considerable attention from both scholars and practitioners in the fields of human resource development (HRD), organization development (OD), psychology, and business. In spite of this popularity, there is a scarcity of empirical research on work engagement in the academic literature. The relationship between work engagement and performance, in particular, is deserving of attention given our field's focus on performance improvement. In this article, we review and analyze relevant research and then propose a research agenda to guide future research on this topic. Conclusions and implications for HRD and OD are discussed.